Small scale industry in Sarawak and its future role in the state economy / Talip Zulpilip ... [et al.] - Zulpilip, Talip; Syawe, Iris Seh Ling (Institut Teknologi MARA Cawangan Sarawak, 1990)
Small Scale Industry (SSI) is an important and integral part of the economy of Sarawak. Furthermore, SSI will continue to play a meaningful role in the overall economic development of the State. Recently, the Ministry of Industrial Development in Sarawak and MARA Institute of Technology, Sarawak Branch have jointly made a study of the Small and Medium Industries (SMIs) in Sarawak. The study is very comprehensive as it covers about 79.1% of the manufacturing establishments in Sarawak. The data collected provide a clear scenario of these establishments in terms of their profile, production, marketing, problems, manpower and training. Whether being categorised by existing paid-up capital or employment size, the majority of the manufacturing establishments in Sarawak are SSI.